Regional trade and international production networks: The context of automobile industry in Asia. (30th April 2011) - De, Debdeep
The dynamics of regional development has moved on in analysing the complex relationship in the changing international production networks (IPNs). Regional integration in these days is limited in not only the formation of regional trade agreements and free trade agreements which has emerged in facilitating the economic cooperation with the stagnation in WTO but also a complex strategic coupling of those economic factors linking the industries operating in specific regions to their counterparts orchestrating production networks on a global basis. Development of automotive industry, covering automobile vehicle and component manufacturing, is usually in the interest of policymakers in developing Asian countries. Promotion of the automotive industry can lead to the expansion of numerous complementary investments by auto parts firms, thereby laying down the basis for broad-based industrial growth. With the increased global competition and the emergence of Asia as the regional automobile hub, there is a need for understanding the industry dynamics in the context of IPNs built on this regional frame. Policy domain is conducive to maintain economic and policy environment in the entire region as well as to strengthen absorptive capability of indigenous manufacturers in regional trajectories. Thus this article tries to identify the linkages in the production networks and the trade agreements in the context of the automobile industry. The key issue is how the growing formal trade agreements influence the IPNs which had been established and working relatively perfectly in the region. This article analyses the intraregional trade in the automobile industry in Asia which is essentially empirical in design but the empirical analysis is carried out in the context of the existing literature. This article concludes with the fact that regionalism can in fact trigger the formation of the networks, thus facilitating the regional industrial growth.